Impregnation of K+ Over Deoiled Spent Bleaching Clay (SBC) as a Catalyst in Transesterification - Rehan, Zainol Abidin; Gaanty Pragas, Maniam; Mohd Hasbi, Ab. Rahim (2016)
World energy demand expected to increase as a result of blossoming urbanisation, better living standards and rising human population. Biodiesel becomes an important alternative energy as the price and demand of fossil fuel in the global market is increasing each day. It has become obvious that biodiesel can create a generous contribution to the future energy demands as it brings less pollution to environment if compared to fossil fuels. There are many different types of potential feedstock and catalyst for biodiesel production. Compared to edible oil and non-edible vegetable oils as a feedstock, natural waste is very much considered as a biodiesel feedstock because of the huge demand for edible oils as a food source. Moreover, the uses of natural waste oils as a feedstock and catalyst from wastes are more cost effective. Therefore, production of biodiesel from natural waste is the best way to overcome all the associated problems with edible oils. In this present study, waste cooking oil (WCO) and impregnation of K + over deoiled spent bleaching clay (SBC) as a catalyst (K + impregnated DSBC) were attempted. In this study, K + impregnated DSBC was obtained from impregnation of 60 % potassium hydroxide (KOH) into deoiled SBC, dried in oven at 100 °C for 16 hours and finally calcined on furnace at 500 °C for 4 hours. The prepared catalyst is characterized by several methods such as TGA, XRD, XRF, FESEM and FTIR. Result from transesterification showed that highest methyl esters (ME) content was at 91.8 % with 5 h reaction duration at 65 ± 2 °C. Optimization of reaction revealed that 12:1 methanol to oil ratio and catalyst amount of 7 wt.% as optimal reaction conditions. Furthermore, catalyst can be reused up to 5 times while maintaining ME conversion at 70 ± 0.2 %.